ANALISIS DAMPAK PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN (PUAP) TERHADAP PENINGKATAN PENDAPATAN PETANI - Iim Mucharam; M.Muslich Mustadjab; Djoko Koestiono (Universitas Teuku Umar, 2016)
This study is aimed to analyze the impact of Rural Agribusiness Development Program (PUAP) to increase the income of Consolidated Farmers Group (Gapoktan) PUAP in Jember. This research was conducted by survey method with the farmer population under study is divided into two, namely the members Gapoktan PUAP receiver and not the recipient PUAP Gapoktan members. Analytical approach used is the with and without method using a cross section data of PUAP Gapoktan members and non members. The method of analysis used is multiple regression analysis, the average of different test and Importance Performance Analysis. The results showed that the PUAP program can increase farmers income.